Exposure to ambient air pollution and the incidence of lung cancer and breast cancer in the Ontario Population Health and Environment Cohort. Issue 9 (30th July 2019) - Bai, Li; Shin, Saeha; Burnett, Richard T.; Kwong, Jeffrey C.; Hystad, Perry; van Donkelaar, Aaron; Goldberg, Mark S.; Lavigne, Eric; Weichenthal, Scott; Martin, Randall V.; Copes, Ray; Kopp, Alexander; et al.
Abstract : Lung and female breast cancers are highly prevalent worldwide. Although the association between exposure to ambient fine particulate matter (PM2.5 ) and lung cancer has been recognized, there is less evidence for associations with other common air pollutants such as nitrogen dioxide (NO2 ) and ozone (O3 ). Even less is known about potential associations between these pollutants and breast cancer. We conducted a population‐based cohort study to investigate the associations of chronic exposure to PM2.5, NO2, O3 and redox‐weighted average of NO2 and O3 (Ox ) with incident lung and breast cancer, using the Ontario Population Health and Environment Cohort (ONPHEC), which includes all long‐term residents aged 35–85 years who lived in Ontario, Canada, 2001–2015. Incident lung and breast cancers were ascertained using the Ontario Cancer Registry. Annual estimates of exposures were assigned to the residential postal codes of subjects for each year during follow‐up. We used Cox proportional‐hazards models adjusting for personal‐ and neighborhood‐level covariates. Our cohorts for lung and breast cancer analyses included ~4.9 million individuals and ~2.5 million women, respectively. During follow‐up, 100, 146 incident cases of lung cancer and 91, 146 incident cases of breast cancer were diagnosed. The fully adjusted analyses showed positive associations of lung cancer incidence with PM2.5 (hazard ratio [HR] = 1.02 [95% CI: 1.01–1.05] per 5.3 μg/m 3 ) and NO2 (HR = 1.05 [95% CI: 1.03–1.07] per 14 ppb). No associations with lung cancer were observed for O3 or Ox . Relationships between PM2.5 and NO2 with lung cancer exhibited a sublinear shape. We did not find compelling evidence linking air pollution to breast cancer. Abstract : What's new? Although exposure to ambient fine particulate matter has been associated with lung cancer, there is less evidence for associations with other common air pollutants such as NO2 and O3. Even less is known about potential associations between these pollutants and breast cancer. In this large population‐based cohort study in Ontario, Canada, exposures to PM2.5 and NO2 but not O3 were associated with increased lung cancer incidence. Using a newly developed class of concentration‐response models, the authors observed sublinear relationships of PM2.5 and NO2 with lung cancer. No strong evidence of a relationship between air pollutants and breast cancer was observed.